DEEP EUTECTIC SOLVENT PULPING FROM SORGHUM STALKS - Gülsoy, Sezgin Koray; Küçüle, Aysun; Gençer, Ayhan; Gülsoy, Sezgin Koray; Gençer, Ayhan (Universidad del Bio-Bio, 2022)
Deep eutectic solvents are characterized as natural, green, biodegradable, non-flammable, non-volatile, non-toxic, odorless, colorless, easy to prepare, and easy to recycle after use. They present an opportunity to introduce new techniques for the pulping process. This study investigated the possibility of using a green deep eutectic solvents from sorghum stalks for pulp and paper production. Choline chloride/ethylene glycol was used in the preparation of eutectic mixtures in molar ratios of 4/10, 5/10, and 6/10. These eutectic mixtures were then applied as cooking liquor to sorghum stalks at two different cooking times (140 and 160 minutes). In addition, the traditional pulping methods of soda and kraft cookings were carried out using sorghum stalks and the pulps were compared with the deep eutectic solvents pulps. The results showed that the pulp production using deep eutectic solvents was accomplished successfully. Some properties of deep eutectic solvents pulps were comparable to those of the soda and kraft pulps. deep eutectic solvents can play an essential role in cleaner pulp production © 2022 Elsevier B.V., All rights reserved.
Keywords: Choline Chloride; Deep Eutectic Solvent; Ethylene Glycol; Green Chemistry; Pulp; Sorghum